Use of airborne laser scanner data in demanding forest conditions - Maguya, Almasi S. (Lappeenranta University of Technology, 2023)
Thesis for the degree of Doctor of Science (Technology) to be presented with due permission for public examination and criticism in Auditorium 1382 at Lappeenranta University of Technology, Lappeenranta, Finland on the 21st of December, 2015, at 12:00 p.m.